2022
DOI: 10.2340/jrm.v53.1122
|View full text |Cite
|
Sign up to set email alerts
|

Use and Usability Of Custom-Made Knee-Ankle-Foot Orthoses In Polio Survivors with Knee Instability: A Cross-Sectional Survey

Abstract: Objective: To investigate the use of custom-made knee-ankle-foot-orthoses in daily life and differences in usability factors of knee-ankle-foot-orthoses between users and discontinued users. Design: Cross-sectional survey study. Subjects: A total of 163 polio survivors provided with a knee-ankle-foot-orthosis at an outpatient clinic of a university hospital. Methods: Use and usability of knee-ankle-foot-orthoses in daily life were assessed with a postal questionnaire. Usability factors were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
2
2
0
Order By: Relevance
“…Considering that our study compared specialist care AFOs to a variety of UC orthoses as provided in clinical practice, rather than walking with shoes as in previous studies, the improvements found can be considered meaningful. For specialist care KAFOs, the effects on perceived stability and satisfaction are in line with earlier improvements found for specialist care carbon composite KAFOs [ 23 , 49 ]. When compared to objectively measured walking ability in a gait laboratory, perceived effects such as safety while walking on irregular surfaces may be more representative of walking in daily life and therefore of greater importance to patients.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Considering that our study compared specialist care AFOs to a variety of UC orthoses as provided in clinical practice, rather than walking with shoes as in previous studies, the improvements found can be considered meaningful. For specialist care KAFOs, the effects on perceived stability and satisfaction are in line with earlier improvements found for specialist care carbon composite KAFOs [ 23 , 49 ]. When compared to objectively measured walking ability in a gait laboratory, perceived effects such as safety while walking on irregular surfaces may be more representative of walking in daily life and therefore of greater importance to patients.…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, these improvements may have contributed to the shift in functional ambulation level, which increased with a specialist care orthosis from 8% to 19% full community walkers, although the increased use of walking aids at follow-up should be considered in this shift. Mean satisfaction scores with the specialist care orthosis were comparable with previous studies using the D-QUEST [ 26 , 49 , 50 ].…”
Section: Discussionsupporting
confidence: 78%
“…Although the benefits of swing phase knee motion provided by SC-KAFO are evident, the L-KAFO remains the most prevalent orthotic intervention for patient in need of a KAFO (7)(8)(9). L-KAFO must be prescribed in the presence of hip or knee flexion contractures >10 degrees, leg length discrepancy >15 cm, genu varum/valgum >10 degrees, body weight >125 kg, hip musculature strength <grade 3 (fair), the need for ischial weightbearing, cognitive and psychological disorders, and those with bilateral motor impairment or flail lower limbs (8,9). However, most patients devoid of these limitations are not prescribed SC-KAFO primarily due to cost and the need for training, predisposing the wearer to iatrogenic consequences associated with long-term use.…”
Section: Introductionmentioning
confidence: 99%
“…Total knee and hip replacements address overused, weakened lower extremities. [10][11][12][13][14][15] There is no cure for polio, but it can be prevented with safe and effective vaccination. Inactivated poliovirus vaccine (IPV) given by I.M.…”
mentioning
confidence: 99%